Understanding emotional intelligence - Lanthem, John T. (Psychology research progress, 2021)
"This book looks at the topic of emotional intelligence from a variety of perspectives, including adolescence, bullying, intimate relationships, and more. Chapter One describes the origin of the concept of emotional intelligence, the change and evolution of emotional intelligence throughout childhood and adolescence, and reviews published findings on the relationship of emotional intelligence with socio-emotional adjustment and bullying behavior. Chapter Two analyzes the role that emotional intelligence might play in establishing effective, stable, healthy, and happy intimate relationships. The third chapter provides a synthesized historical overview of the notion of emotions and the nature of their relationship to the rational mind and analyzes how concepts of "rational" and "emotional" can co-exist. Following this, the fourth chapter explores how the research area of emotional intelligence can be leveraged to prevent bullying victimization and peer aggression. Chapter Five deals with the practical implications of emotional intelligence for work and health. Chapter Six details how levels of physical activity correlate with emotional intelligence in adolescents. Lastly, the final chapter addresses the question of whether self-compassion can predict future anxiety and depression"--